Герой небесної сотні Євген Миколайович Котляр - Бадєєва, Л. І.; Проскурін, В. О. (ХНУРЕ, 2025)
The question is relevant, because Yevhen Kotlyar gave his life defending the rights and freedoms of Ukrainian citizens. This is an attempt to summarize the already known material about Yevhen's life path, using information from documentaries about the hero, as well as the memories of relatives, friends, and comrades. The author also recorded a new interview with the hero's father, memories of Yevhen's former classmates and like-minded comrades from the environmental organization "Green Front".
Keywords: герой; Yevhen Kotlyar